2017
DOI: 10.1111/joa.12629
|View full text |Cite
|
Sign up to set email alerts
|

Interdigital tissue remodelling in the embryonic limb involves dynamic regulation of the miRNA profiles

Abstract: Next-generation sequencing in combination with quantitative polymerase chain reaction analysis revealed a dynamic miRNA signature in the interdigital mesoderm of the chick embryonic hinlimb in the course of interdigit remodelling. During this period, 612 previously known chicken miRNAs (gga-miRNAs) and 401 non-identified sequences were expressed in the interdigital mesoderm. Thirty-six microRNAs, represented by more than 750 reads per million, displayed differential expression between stages HH29 (6 id) and HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Role in interdigital tissue remodeling in the embryonic limb [30] Role in chondrocyte development [31][32][33]…”
Section: Early Embryo Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Role in interdigital tissue remodeling in the embryonic limb [30] Role in chondrocyte development [31][32][33]…”
Section: Early Embryo Developmentmentioning
confidence: 99%
“…miRNAs have been found to play relevant roles in several fundamental developmental processes among which gametogenesis, preimplantation and early embryonic development, neurogenesis and somitogenesis [8,9,29,30,106,107]. As a consequence, their expression during development needs to be tightly regulated in time and space.…”
Section: The Mir-181 Family In Development and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The other miRNA, miR-133c-3p, that was abundantly expressed in chicken breast muscle [ 19 ], enhances skeletal muscle proliferation and differentiation by repressing SRF [ 11 ]. Similarly, miR-21 and miR-146c have been recently identified as miRNAs upregulated in chicken interdigital regression and associated with inflammation, cell senescence, and programed cell death [ 20 ]. Additionally, a previous study reported upregulated expression of miR-21 in breast muscle of low body weight chickens [ 9 ].…”
Section: Discussionmentioning
confidence: 99%